(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article analyzes the results of surgical treatment of a 61-year-old patient named M., who had VC3-4 (3.0mm), VC4-5 (3mm), VC5-6 (3mm), VC6-7 (3.0mm) intervertebral disc herniation, which involved removal of all intervertebral discs in the cervical spine and implantation of a “PEEK” cage implant. The extent to which the dynamics of clinical and neurological symptoms changed 3 months after the operation, the general clinical neurological condition of the patient, and changes in the range of motion in the arms and legs were recorded.